Adenoma Detection Rates in 45–49-Year-Old Persons Undergoing Screening Colonoscopy: Analysis From the GIQuIC Registry. (15th May 2022) - Bilal, Mohammad; Holub, Jennifer; Greenwald, David; Pochapin, Mark B.; Rex, Douglas K.; Shaukat, Aasma
Abstract : INTRODUCTION: The impact of lowering the colon cancer screening age from 50 to 45 years on the endoscopist adenoma detection rate (ADR) is not well studied. METHODS: We used average-risk screening colonoscopies submitted to the GI Quality Improvement Consortium registry from 2014 to 2020 among individuals aged 45–75 years. We used the 1-way ANOVA test to determine differences between ADRs among 45–49-year-old, 50–54-year-old, and 50–75-year-old individuals. RESULTS: A total of 2, 806, 539 screening colonoscopies were performed by 814 endoscopists. The mean ADR in the 45–49-year-old group was 28.6% compared with 31.8% for the 50–54-year-old group ( P < 0.001) and 36.3% for the 50–75-year-old group ( P < 0.001). DISCUSSION: Endoscopists might see a small drop in their ADR once a higher proportion of 45–49-year-old patients start undergoing screening colonoscopy.